Introduction of the European experience of digital administration in the practice of managing domestic construction projects - Prykhodko, O.; Nikolaev , G. (Ways to Improve Construction Efficiency, 2023)
The article is devoted to the substantiation of the content and regulation of organizational and technological measures to ensure biosferous construction on the basis of the experience of applying the ecologically-oriented methodology of territorial planning. The design decision to ensure the functional and technological reliability of developers of construction projects from the standpoint of the possibility of implementing the functions of biosphere-compatible construction and implementation of innovative design and architectural-planning solutions is analyzed. The problems and the main ecological and urban planning principles of the organization of the key forms of resettlement - urban agglomerations are considered. The method of planning organization of systems of interrelated resettlement taking into account ecological and city-planning conditions on the basis of organizational and technological estimation of biosphere compatibility of settlements from the standpoint of efficiency of building technologies of architectural and urban complex is proposed. The introduction of European experience in digital administration in the management of domestic construction projects in Ukraine is becoming an important area for the development of modern infrastructure and improving the quality of construction projects. This article traces the key aspects of the implementation of European standards and practices of digital administration in the management of construction projects in Ukraine. The article analyzes strategies for adapting and implementing digital tools such as Building Information Modeling (BIM), electronic document management and online monitoring systems that can increase the efficiency and transparency of project management. The advantages of using digital technologies in the planning, execution and control of construction projects are discussed, in particular, in terms of reducing costs, increasing the accuracy and speed of decision-making. Examples of successful implementation of European practices in construction management in different countries and possible ways of their adaptation to the conditions of the Ukrainian construction market are analyzed in detail. This analysis helps to determine the optimal strategies and approaches for the successful implementation of digital administration in construction project management in Ukraine.